Gastrointestinal stromaal tumor (GIST) in the jejunum: Tumor del estroma gastrointestinal (GIST) en yeyuno - Mantilla , Jose (2023)
Gastrointestinal stromal tumors (GIST) are mesenchymal neoplasms that represent less than 3% of gastrointestinal neoplasms, with an incidence of 1 to 2 cases per hundred thousand inhabitants. It originates more frequently in the stomach and small intestine and is characterized by the expression of the tyrosine kinase growth factor receptor, CD117. Therefore, its diagnosis requires an immunohischemical study to rule it out from other mesenchymal tumors. However, enteroscopic imaging and analysis of the biopsy may suggest a preoperative diagnosis of probable GIST. The case of a 62-year-old woman with rectorrhagia and recurrent anemia caused by mid-intestinal bleeding observed by capsule endoscopy is reported. Enteroscopy revealed a subepithelial ulcerated lesion in the proximal jejunum, and a biopsy was taken, the anatomopathological study of which suggested a gastrointestinal stromal tumor. The biopsy sample subjected to immunohistochemical studies confirms the suspicion of a cKit/CD117-positive GIST tumor. Surgical resection of the tumor with dimensions 4.2x3 cm is performed. After surgery, the patient was stable and under clinical follow-up until she was discharged. Clinical finding